(untitled) (Fiep Bulletin - online, 2017)
The physical fitness of young people has been widely studied. The importance of good motor development for theeducation of the body as well as the overall development of the person lies in its preventive role in school difficulties. The purposeof this cross - sectional descriptive study was to perform a survey of motor performance indicators of the students of a privateschool in the neighborhood of the Tabuleiro, located in the city of Maceió - AL. The sample consisted of 14 students, 8 boys and 6girls. For data collection, the tests of the PROESP-BR manual, composed of tests that estimate the physical fitness and the motorperformance of children and adolescents, were used. The results showed that the vast majority are classified as very physicallyweak. The low results indicate that the students studied are in need of an improvement in motor performance, whichdemonstrates the need to introduce in Physical Education classes activities that promote the improvement of the physicalcapacity and agility of the students, resulting in an improvement in the Avoiding the development of diseases related to lack ofphysical activity.